2016
DOI: 10.1007/978-3-319-38810-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Both Free Radical Scavenging Capacity and Antioxidative Damage Effect of Polydatin

Abstract: Cellular damage such as oxidation and lipid peroxidation, and DNA damage induced by free-radicals like reactive oxygen species, has been implicated in several diseases. Radicals generated by 2,2-azobis (2-amidino-propane) dihydrochloride (AAPH) are similar to physiologically active ones. In this study we found that polydatin, a resveratrol natural precursor derived from many sources, has the capacity of free radical scavenging and antioxidative damage. Using free radical scavenging assays, the IC50 values of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The presence of inflammatory processes in mNSCLC patients may be related to the presence of malignancy itself, to concomitant smoke-associated bronchopulmonary chronic disease and to the presence of relapsing bacterial infections related to incomplete integrity the airways (44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammatory processes in mNSCLC patients may be related to the presence of malignancy itself, to concomitant smoke-associated bronchopulmonary chronic disease and to the presence of relapsing bacterial infections related to incomplete integrity the airways (44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Among which, the 4′-hydroxyl group is the preferred reaction site as a result of the resonance effects that occur between the two aromatic rings [ 40 42 ]. Therefore, PD can quench a variety of free radicals produced both in vitro and in vivo , including 2,2-diphenyl-1-picryl-hydrazyl, 2,2-azobis (2-amidino-propane) dihydrochloride, superoxide anion, hydrogen peroxide, and hydroxyl radicals [ 27 , 43 , 44 ]. Notably, Fabris et al [ 45 ] showed that PD is a suitable compound for the prevention and control of the lipid peroxidation because of its lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…These properties provide PD better bioavailability than resveratrol. PD retains powerful free radical scavenging property, and also exhibits anti‐oxidant functions . PD was also shown to exert cardioprotective effects against ischemia/reperfusion injury .…”
Section: Introductionmentioning
confidence: 99%